Naturalistic parent–child reading frequency and language development in toddlers with and without autism. (November 2022) - Mathée-Scott, Janine; Ellis Weismer, Susan
Background and aims: The efficacy of parent–child reading for supporting language development has been well-established in the neurotypical (NT) literature. For children with autism spectrum disorder, (ASD) who may be at risk for delays in language development, prior research has shown promise for shared book-reading interventions. Yet there has been limited research on naturalistic parent–child reading with autistic children to date. The present study aimed to fill this missing link in the current literature. Methods: Fifty-seven autistic toddlers participated at two developmental time points: Time 1 ( M age = 30.4 months) and Time 2 ( M age = 43.8 months). An NT control group ( N = 31) was matched on age to a subset of the ASD group ( N = 33). We assessed group differences in parent–child reading frequency between age-matched NT and autistic groups. Using a one-year follow-up design, we evaluated the relationship between parent–child reading and autistic children's language development. Results: Cross-group comparisons revealed that parents of age-matched NT children reported significantly more frequent weekly parent–child reading than parents of autistic toddlers. After a one-year follow-up with the autistic group, within-group analyses revealed that greater frequency of parent–child reading (controlling for maternal education, books in the home, and autism symptom severity) was associated with larger growth in autistic toddlers' receptive and expressive language skills. Conclusions and implications: These findings have important clinical implications as they emphasize the potential of parent–child reading for supporting autistic children's language development. Findings demonstrate that frequency of parent–child reading is associated with language development over one year. Findings also demonstrate that parents of autistic children engage in less frequent parent–child reading than parents of age-matched NT peers, suggesting these parents may face more barriers to implementing parent–child reading than parents of NT children.